ANALISIS PRODUKTIVITAS PENGGUNAAN ALAT BERAT PEKERJAAN TIMBUNAN PILIHAN PADA PEMBANGUNAN JALAN - MA'RIFAH, FAIZAH RIFFAT (KURVA S JURNAL MAHASISWA, 2020)
Road construction Simp.3 Km.8 Beno Harapan - Kantor Camat Batu Ampar Kutai Timur Regency is a project aimed at facilitating transportation that leads to Batu Ampar subdistrict in Kutai Timur Regency. This research focuses on earthworks in the form of selected pile works. In this work the heavy equipment used are Excavators, Dump Trucks, Motor Graders, Roller Vibrators, and Water Tanks. This research uses quantitative descriptive methods. The analysis carried out is the calculation of cycle time, calculation of productivity of heavy equipment, calculation of the time of use of the tool, calculation of the cost of using the equipment, and scheduling of use of the tool. The results of this study are the excavator productivity is 33,826 m3 / hour, dump truck is 3,972 m3 / hour, motor grader is 0.59 hours, a vibrator roller of 7,995 m3 / hour, and water tank of 49,263 m3 / hour. The total time for using the tool is 13 weeks and the total cost for using the tool is 813,382,282 Rupiah.